The power of place world regional geography : study guide - Latz, Gil (Annenberg/CPB Project, 1996)
This collaborative effort by an international team of geographers and educational broadcasters features a series of stories that explores the geographical forces shaping our world. The contributors provide penetrating insights into a range of geographic issues around the globe.